Variation in growth and N2 fixation within and among Centrosema spp. in response to phosphorus supply - Cadisch, Georg; Sylvester-Bradley, Rosemary; Nosberger, J (1992)
Four inoculated ecotypes of each of Centrosema acutifolium, C. brasilianum and C. macrocarpum were grown in undisturbed soil (oxisol) cores in a glasshouse to study their response to 7 phosporus levels (a total of 11, 22, 45, 90, 180, 360 and 720 mg/core P, surface applied as Ca(H2PO4)2.H2O). Seven weeks after planting, dry matter production, leaf area, N yield, nodulation, nodule-P concentration and acetylene reduction activity increased strongly with P supply. Enhanced leaf area was due mainly to increases in individual leaf size, especially in the large-leaved C. macrocarpum. Shoot-N concentration of all species increased with P supply, which was attributed to increased nodule mass and N2 fixation, but not to a greater proportion of leaf material. The response to P supply in leaf number, leaf size and leaf-to-stem ratio as well as nodule number and weight differed among species. However, there was no significant (P > 0.05) species × P rate interactions for dry matter and N yield, shoot-N %, or nodule-P %, but strong intra-specific variation was found. All 3 Centrosema species contain important genetic variability in the growth and N2 fixation responses to P supply during establishment. Therefore both parameters should be taken into account in selecting ecotypes.